Analisis Kesesuaian Lahan untuk Bidang Pertanian pada Komoditas Tanaman Jagung (Studi Kasus: Kecamatan Lubuk Alung, Kabupaten Padang Pariaman) - Almuhazibi, M.; Hermon, Dedi (Lembaga Yasin AlSys, 2024)
Land is an important part of human life because it is where all human activities and lives take place. Many factors, including living things, hydrology, soil and climate, affect land. This study aims to evaluate the suitability and production of corn crops in Lubuk Alung Sub-district, Padang Pariaman Regency. This research uses a quantitative approach by using the scoring method to analyze the suitability of land for corn crops in Lubuk Alung Sub-district, Padang Pariaman Regency. The results of the research are known without using land units as a reference for the assessment of the distribution of land suitability classes for corn crops in the highly suitable class (S1) 1,110.34 ha, suitable class (S2) 11,092.62 ha, marginally suitable class (S3) 2,593.24 ha, and unsuitable class (N) 433.63 ha. While using the land unit as a reference for assessing the distribution of land suitability classes for corn crops in the highly suitable class (S1) 827.01 ha, suitable class (S2) 5,047.73 ha, marginally suitable class (S3) 1,598.06 ha, and unsuitable class (N) 7,757.04 ha. From the estimation of production yield calculation, it is known that on land with a very suitable suitability class (S1) the production yield reaches 19,753.7 kg/ha, suitable class (S2) the production yield reaches 16,833.6 kg/ha, marginal suitable class (S3) the production yield reaches 14,892.5 kg/ha, and unsuitable class (N) the production yield reaches 14,146.3 kg/ha.